The Utilization of Information and Communication Technology among Islamic Secondary School Teachers in Malaysia - Rashid, Adnan Abd (SOSIOHUMANIKA, 2011)
ABSTRACT: Malaysia has implemented the first computer system in 1966. Since then, the government â through Ministry of Education â has introduced various initiatives to facilitate the adoption and diffusion of Information and Communication Technology (ICT). In line with the Vision 2020, Ministry of Education has draft ways so as to integrate ICT into education system. Malaysian government has invested millions of Ringgit for the usage of ICT in education. The investments include the building of computer labs, supplying of PCs, and related peripherals, training of teachers, and development of instructional material. The research will concentrate on the utilization, self-efficacy, integration, and satisfactory level of the Islamic Religious Secondary School teachers of Malaysia. Although there are only 55 of such schools but these schools are actually a sought after schools by parents due to its capability of producing leaders academically as well as spiritually. The study will deal with issues such as self-efficacy, utilization, and training needs/provided as well as the integration of ICT in teaching and learning. The analysis is adopting principle component analysis to determine the predictors of the underlying variables as well the use of Structural Equation Modeling (SEM) to strengthen the analysis. Key words: Information and communication technology, K-economy, teachers of Malaysia, and competences in teaching and learning.About the Author: Assoc. Prof. Dr. Adnan Abd Rashid is Senior Lecturer at the Institute of Education IIUM (International Islamic University of Malaysia), Jalan Gombak, 53100 Kuala Lumpur, Malaysia. He can be reached at: adnan@iiu.edu.my and arashid@isesco.org.maHow to cite this article? Rashid, Adnan Abd. (2011). âThe Utilization of Information and Communication Technology among Islamic Secondary School Teachers in Malaysiaâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.4, No.2 [November], pp.145-158. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-0112. Chronicle of article: Accepted (September 15, 2011); Revised (October 20, 2011); and Published (November 20, 2011). Â  Â